The Role of Abutment-Attachment Selection in Resolving Inadequate Interarch Distance: A Clinical Report - Abdullah S. Alsiyabi, BDS, MS;1 and Glenn E. Minsley, DMD2 (Journal of Prosthodontics, 2005)
A critical factor that needs to be evaluated during the diagnosis and treatment planning phase for patients seeking an implant-tissue-supported overdenture or metal-resin implant fixed denture is the presence of adequate interarch distance